APLIKASI MICROCONTROLLER ATMEGA2560 SEBAGAI RANCANGAN KONTROL OTOMATIS PENYEMPROTAN KAPORIT DAN KAPUR TOHOR PADA BAK PENJERNIHAN WATER TREATMENT PLANT DI BANDAR UDARA INTERNASIONAL SUPADIO PONTIANAK - Soleman Ricardo Yoppo; Suse Lamtiar; Inof Seno Acton (Politeknik Penerbangan Indonesia Curug, 2019)
The water treatment plant of Pontianak Supadio International Airport has 3 purification tanks, each of which purification tanks 1 and 2 function for the purification process and in the third purification tub it is used as a temporary reservoir of processed water from the purification tank 1 before distribution, 1 size purification tub 127.5 m3 of a 2 m purification tank measuring 225 m3 was separated by an inspection line into two parts, each measuring 127.5 m3. Every day in the 1st bath tub and purification tank 2 the mixing process of chlorine and calcium lime is carried out when the water in the tub is full, chlorine and calcium lime are mixed manually using a bucket or container as a chlorine and quicklime container mixed with water then after that the chlorine and calcium lime liquid is poured manually into the purification tub. Therefore there needs to be development by reversing an automated tool to assist the technician's work and to make time efficient, a tool that will be used to function automatically mixing chlorine and calcium lime which has been determined to be in the purification tank.